A walking tour in Southern France Ezra Pound among the Troubadours - Pound, Ezra 1885-1972 (New Directions Publ. Corp., 1992)
In the course of transcribing and emending the text of "Walking Tour 1912," editor Richard Sieburth retraced Pound's footsteps along the roads to the troubadour castles. "What this peripatetic editing process...revealed," he writes, "was a remarkably readable account of a journey in search of the vanished voices of Provence that at the same time chronicled Pound's gradual discovery of himself as a modernist poet....